How does the recurrence-related morphology characteristics of the Pcom aneurysms correlated with hemodynamics? - Hu, Xiaolong; Deng, Peng; Ma, Mian; Tang, Xiaoyu; Qian, Jinghong; Wu, Gang; Gong, Yuhui; Gao, Liping; Zou, Rong; Leng, Xiaochang; Xiang, Jianping; Wu, Jiandong; et al. (Frontiers in Neurology, 2023)
Posterior communicating artery (Pcom) aneurysm has unique morphological characteristics and a high recurrence risk after coil embolization. This study aimed to evaluate the relationship between the recurrence-related morphology characteristics and hemodynamics. Method A total of 20 patients with 22 Pcom aneurysms from 2019 to 2022 were retrospectively enrolled. The recurrence-related morphology parameters were measured. The hemodynamic parameters were simulated based on finite element analysis and computational fluid dynamics. The hemodynamic differences before and after treatment caused by different morphological features and the correlation between these parameters were analyzed. Result Significant greater postoperative inflow rate at the neck (Qinflow), relative Qinflow, inflow concentration index (ICI), and residual flow volume (RFV) were reported in the aneurysms with wide neck (>4mm). Significant greater postoperative RFV were reported in the aneurysms with large size (>7mm). Significant greater postoperative Qinflow, relative Qinflow, and ICI were reported in the aneurysms located on the larteral side of the curve. The bending angle of the internal carotid artery at the initiation of Pcom (αICA@PCOM) and neck diameter had moderate positive correlations with Qinflow, relative Qinflow, ICI, and RFV.The morphological factors, including aneurysm size, neck diameter, and αICA@PCOM, are correlated with the recurrence-inducing hemodynamic characteristics even after fully packing. This provides a theoretical basis for evaluating the risk of aneurysm recurrence and a reference for selecting a surgical plan.